Impact of musculoskeletal disorders on quality of life of patients visiting tertiary care hospital. - Shah Khalid; Sayed Zulfiqar Ali Shah; Abid Ali Khalil; Ihsan Ullah (Journal of the Pakistan Medical Association, 2021)
Objective: To determine the impact of musculoskeletal disorders on quality of life of patients visiting Khyber Teaching Hospital, Peshawar. Method and Material: A cross sectional survey conducted in Khyber Teaching Hospital, Peshawar from September 2018 to March 2019 using a validated EQ-5D quality of life scale. The survey questionnaire was attended by 377 respondents having variety of musculoskeletal disorders (MSDs). EQ-5D can be effectively used for assessing the quality of life and health status using the VAS pain scale. Results: There were total 377 respondents. Mean age of the participants was 35.9 ± 12.5 years. Out of 377 participants, 204 (54.1%) were male, while 173 (45.9%) were female. Muscular weakness was the most commonly encountered problem (40.6%), followed by muscle stiffness (13.0%) and adhesive capsulitis (10.3%). The remaining respondents were having different kinds of MSDs. Patients with MSDs were having significantly moderately low score on EQ-5D. Conclusion: The finding of this study suggests that MSDs have negative impact on quality of life and health status of the sufferers. Individuals having any sort of MSDs should seek proper care in order to improve their quality of life, health status and work performance. Key words: Musculoskeletal Diseases, Health, Quality of Life, visual analog scales, Cross Sectional Studies. Continuou....